Assessment of Nutritional Status in Children with Cerebral Palsy - Mohana (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Cerebral palsy refers to a group of disorders that affect movement or posture. The present study was conducted to nutrition status in children with cerebral palsy.Subjects and Methods:The present study was conducted on 120 children age ranged 7-16 years diagnosed with cerebral palsy. Nutritional status assessment was based on the TSF and AFA estimates derived from TSF and mid-upper arm circumference (MUAC) measurements. Children were classified into underweight, <5th normal weight, 5-84.89th and overweight, >85th.Result:There were 70 boys and 50 girls in present study. Common type was spastic in 90, dyskinetic in 20 and ataxic in 10 patients. GMFCS levels was level I in 30, level II in 15, level III  in 18, level IV in 9 and level V in 48 patients. The mean TSF and AFA Z-scores were significantly lower in low functioning children than in moderate functioning children (P< 0.05).Underweight and overweight prevalence were 13.1 % and 4.9 % respectively. The underweight prevalence was significantly higher in girls than in boys (P< 0.05), whereas overweight prevalence was significantly higher in boys than in girls (P< 0.05). Both underweight (P- 0.148) and overweight (P- 0.421) prevalence was not significantly different across age groups. Underweight prevalence was significantly higher in the low functioning group (P< 0.05).Conclusion:Authors found that cerebral palsy children face nutritional challenges. It is more common in underweight as compared to overweight children.